Not just a work permit: EU citizenship and the consumption behavior of documented and undocumented immigrants - Effrosyni Adamopoulou; Ezgi Kaya (Cardiff University, Cardiff Business School, 2019)
This paper explores the impact of the 2007 European Union enlargement on the consumption behavior of immigrant households. Using data from a unique Italian survey and a difference-in-differences approach, we find that the enlargement induced a significant consumption increase for the immigrant households from new member states both in the short- and in the medium-run. This enlargement effect cannot be attributed to the mere legalization as it concerns both undocumented and documented immigrants, albeit through different channels. Detailed information on immigrants' legal status (undocumented/documented) and sector of employment (informal/formal) allows us to shed light on the exact mechanisms. Following the enlargement, previously undocumented immigrants experienced an increase in the labor income by moving from the informal towards the formal economy, whereas immigrants who were already working legally in Italy benefitted from the increased probability of getting a permanent contract. Enhanced employment stability in turn reduced the uncertainty about future labor income leading to an increase in documented immigrants' consumption expenditure.
Keywords: D12; E21; F22; 330; consumption; citizenship; informality; (un)documented immigrants; work permit